RESOURCE LEVERAGING AND CUSTOMER RETENTION IN UPSCALE RESTAURANTS IN PORT HARCOURT, RIVERS STATE, NIGERIA (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2016)
The study investigated the relationship between resource leveraging and customer retention in upscale restaurants in Port Harcourt, Rivers State, Nigeria. The specific objectives were to determine the relationship between resource leveraging and the three measures of customer retention: low customer defection, repeat purchase and high referrals respectively. The study adopted quasi-experimental design which employed survey approach gathered data from 144 senior employees in the 24 upscale restaurants in Port Harcourt. A well-structured questionnaire containing 19 items, inclusive of three demographic items was used to elicit primary data from the respondents. The inferential statistical analysis was conducted with the help of Statistical Package for Social Sciences (SPSS). The result of the inferential statistical analysis showed that resource leveraging had positive and significant relationship with low customer defection(very high), repeat purchase (moderate) and high referrals (weak) respectively. The study concluded that the ability by organizational managers to do more with little resources at their disposal is of strategic imperative to organizational success through customer retention. It was therefore recommended that organizational managers should develop skills in effective resource utilization for enhanced firm performance.